Effects of Levothyroxine Treatment on Lipid Profile in Subclinical Hypothyroidism: A Randomized Clinical Trial: - Naseri, Rozita; Shahebrahimi, Karoon; Kalantarian, Tahereh Sadat; Rahimi, Mehrali; Najafi, Farid; Derakhshandeh, Katayoun; Sharifi, Azam (Galen Medical Journal, 2015)
Background: Studies demonstrated controversial results on subclinical hypothyroidism (SCH) regarding lipid profile alteration with or without Levothyroxine treatment. The purpose of this study is to investigate the effects of Levothyroxine on serum lipids in SCH. Materials and Methods: One hundred patients with SCH referred to Taleghani hospital in Kermanshah were recruited and randomly assigned into the intervention or the control group. Patients in intervention group received Levothyroxine 50-75 micrograms for three months. Patients in control group received the same placebo with the same dose and duration. Lipid profile was measured before and after the trial and the changes were compared between groups. (IRCT code: 138903244179N1). Results: Triglyceride, Total Cholesterol, LDL, HDL and Lipoprotein-A were measured before and after treatment. None of the factors showed significant difference either between or within groups, before and after the treatment (P<0.05). Conclusion: Treating with Levothyroxine does not have any clinically significant impact on lipid profile in SCH patients which indicates that we should not expect SCH patients to use Levothyroxine solely for lipid profile alternation, except those with other clinical indications for treatment.[GMJ.2015;4(2):72-77]